BabA dependent binding of Helicobacter pylori to human gastric mucins cause aggregation that inhibits proliferation and is regulated via ArsS - Skoog, Emma C. (Sci Rep, 2017)
Mucins in the gastric mucus layer carry a range of glycan structures, which vary between individuals, can have antimicrobial effect or act as ligands for Helicobacter pylori. Mucins from various individuals and disease states modulate H. pylori proliferation and adhesin gene expression differently. Here we investigate the relationship between adhesin mediated binding, aggregation, proliferation and adhesin gene expression using human gastric mucins and synthetic adhesin ligand conjugates. By combining measurements of optical density, bacterial metabolic activity and live/dead stains, we could distinguish bacterial aggregation from viability changes, enabling elucidation of mechanisms behind the anti-prolific effects that mucins can have. Binding of H. pylori to Le(b)-glycoconjugates inhibited the proliferation of the bacteria in a BabA dependent manner, similarly to the effect of mucins carrying Le(b). Furthermore, deletion of arsS lead to a decrease in binding to Le(b)-glycoconjugates and Le(b)-decorated mucins, accompanied by decreased aggregation and absence of anti-prolific effect of mucins and Le(b)-glycoconjugates. Inhibition of proliferation caused by adhesin dependent binding to mucins, and the subsequent aggregation suggests a new role of mucins in the host defense against H. pylori. This aggregating trait of mucins may be useful to incorporate into the design of adhesin inhibitors and other disease intervention molecules.